Evaluasi Stabilitas Lereng Pada Struktur Bangunan Penahan Lokasi Gedung C Fakultas Ekonomi Universitas Cenderawasih - Duha Awaluddin Kurniatullah; Hartawan Hasyuar (Fakultas Teknik Universitas Cenderawasih, 2023)
Thus, the slope at Building C of the Faculty of Economics of Cenderawasih University needs to be handled in the form of evaluation or review of the plaster structure (talud), by improving the dimensions, and the slope is analyzed by drained conditions, the slope becomes stable as the slope safety factor changes to 1.557. which according to the safety factor (SF) slope is more than 1.5, and the calculation of Stabilita against shear of slope safety factor is 1,678, which according to safety factor more 1.5. Means that the wall is able to withstand the moment of land that works